Influence of moisture on the interface charge of oil–pressboard composite insulation under DC voltage. Issue 1 (7th February 2018) - Qi, Bo; Jiao, Yanqiu; Gao, Chunjia; Zhang, Shuqi; Zhao, Xiaolin; Li, Chengrong
Abstract : The distortion of the electric field in the oil–pressboard composite insulation caused by the accumulation of the interface charge is detrimental to both the insulation design and operation of converter transformers. The influence of moisture content on the surface charge accumulation of oil–pressboard insulation under DC voltage was studied in this study. In accordance with the Kerr electro‐optic effect, the electric field strengths in transformer oil and the surface charge density were acquired after applying the positive and negative DC voltages in three oil–pressboard insulation models with different moisture content, respectively. The resistivities of the oil and pressboard in three models, namely Model 1# with 3.8–4.2 ppm moisture in oil and 0.35–0.37% moisture in pressboard, Model 2# with 7.6–7.9 ppm moisture in oil and 0.79–0.82% moisture in pressboard and Model 3# with 14.9–15.4 ppm moisture in oil and 1.39–1.42% moisture in pressboard, was also measured. The results indicate that: (i) as negative charges in oil accumulated on the pressboard surface in a much greater speed than the positive ones, the electric field in transformer oil under negative DC voltage decreases more rapidly with time than that under positive DC voltage; (ii) the increase of the moisture content in both oil and pressboard, under either positive or negative DC voltage, leads to the decrease of both the electric field strength in transformer oil and the charge density with time; and (iii) the increase of moisture content could not only decrease the resistivity of both oil and pressboard, but also the ratio of the resistivity between the pressboard and the oil. On the basis of the Maxwell–Wagner theory, the decrease of the ratio between the pressboard and oil could lead to the decrease of the interfacial charge density, leading to the slow transient process of the electric field in transformer oil under DC voltage.